2019
DOI: 10.3390/diagnostics9030076
|View full text |Cite
|
Sign up to set email alerts
|

The Preoperative Predictive Factors for Pathological T3a Upstaging of Clinical T1 Renal Cell Carcinoma

Abstract: We aimed to determine the oncological outcomes of patients with clinical T1 renal cell carcinoma (RCC) upstaged to pathological T3a and to identify the preoperative predictive factors for upstaging. We retrospectively reviewed 272 patients with clinical T1 RCC who underwent surgical treatment. Thirty-three patients (12%) were upstaged to pathological T3a. These patients had a significantly larger tumor size on computed tomography (p < 0.0001), a higher aspartate aminotransferase (AST)/alanine aminotransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
7
3
Order By: Relevance
“…In contrast to our observations, Fukui et al. ( 29 ) reported that level of CRP in the upstaged group was higher than that of the non-upstaged group.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our observations, Fukui et al. ( 29 ) reported that level of CRP in the upstaged group was higher than that of the non-upstaged group.…”
Section: Discussioncontrasting
confidence: 99%
“…There was no difference between the nonand upstaged groups with regard to other clinical parameters including age, gender, BMI, comorbidities, lymphocyte counts, monocyte counts, albumin, globulin, CRP, ACR, PNI, TC and TG. In contrast to our observations, Fukui et al (29) reported that level of CRP in the upstaged group was higher than that of the nonupstaged group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Computed tomography (CT) is the primary staging modality for RCC and is highly effective in distinguishing between cT1 (≤7cm) and cT2 renal tumours (>7cm) 1 . However, the utility of CT imaging in accurately detecting tumour invasion into the renal vein, its segmental branches, or perirenal and/or renal sinus fat—defined as cT3a disease—is limited, 3‐6 lending to reported rates of upstaging specifically to pathologic T3a (pT3a) disease in approximately 10% of all patients initially staged with cT1 RCC 7‐9 …”
Section: Introductionmentioning
confidence: 99%